Implementation of agile SCRUM and Agile UX in the design of the Pelabuhan Ratu application "SI-KIKAN" - Uus Firdaus; Muhammad Dzikri; Himmatul Miftah (Journal of Intelligent Decision Support System (IDSS), 2026)
This study addresses the inefficiency and uncertainty in accessing real-time fish stock information at the Pelabuhan Ratu Fish Market, where traditional manual communication methods remain dominant and hinder effective transactions. The objective of this research is to develop a user-centered mobile application, SI-KIKAN, that provides real-time fish availability information while ensuring high usability for users with diverse levels of digital literacy. This study adopts a design and development approach by integrating Agile Scrum and Agile User Experience (UX) methodologies, enabling iterative system development, continuous user feedback, and adaptive design refinement. Data were collected through field observations, stakeholder interviews, and usability testing involving 30 respondents, and analyzed using qualitative techniques and the System Usability Scale (SUS). The results indicate that the SI-KIKAN application successfully improves information transparency and operational efficiency, as evidenced by a high SUS score of 86.17, categorized as “Excellent,” demonstrating strong usability, learnability, and user satisfaction. The implementation of Agile Scrum facilitated efficient management of development complexity, while Agile UX ensured that the interface design aligned with user needs and field conditions. This study implies that the integration of Agile Scrum and Agile UX is an effective approach for developing user-centered digital solutions in traditional sectors, particularly in improving information accessibility and supporting digital transformation in fisheries markets.